Visual Working Memory in Adolescents with Autism Spectrum Disorder. - Cissne, Mackenzie N.; Bellesheim, Katherine R.; Cowan, Nelson; Christ, Shawn E. (Journal of Autism & Developmental Disorders, 2026)
Previous research suggests that individuals with autism spectrum disorder (ASD) may experience working memory (WM) problems, but the nature of the underlying disruption remains unknown. A recent study (Bodner et al. 2019) found that young adults with ASD experienced intact WM capacity but disruptions in their ability to efficiently filter and allocate attention. The goal of the present study was to extend this work and evaluate potential disruptions in WM capacity and attentional allocation ability in adolescents with ASD. A sample of 38 adolescents with ASD and 39 adolescents without ASD aged 11–15 years completed a computerized WM task. In brief, participants were shown visual arrays consisting of four or six colored stimuli (circles and squares). After a short delay, memory for one of the stimuli was probed. Importantly, participants were informed beforehand that one of the shapes (e.g., circles) was more likely to be probed compared to the other shape (e.g., squares) – thus making it strategically beneficial to focus primarily on the high frequency shapes. The ASD group demonstrated overall lower WM capacity compared to the non-ASD group. However, no group differences were seen in attentional allocation. There was also no evidence of sex-related differences in WM performance in adolescents with ASD. Taken together with previous findings, the current results suggest that adolescents with ASD show disruptions in WM capacity that are resolved by adulthood. Future longitudinal research is needed to further disentangle the component processes of WM and the developmental trajectories of these components.